A high quality method for hemolymph collection from honeybee larvae - Butolo, Nicole Pavan [UNESP]; Azevedo, Patricia; de Alencar, Luciano Delmondes; Domingues, Caio E.C. [UNESP]; Miotelo, Lucas [UNESP]; Malaspina, Osmar [UNESP]; Nocelli, Roberta Cornélio Ferreira [UNESP] (Public Library of Science (PLoS), 2020)
The drastic decline of bees is associated with several factors, including the immune system suppression due to the increased exposure to pesticides. A widely used method to evaluate these effects on these insects' immune systems is the counting of circulating hemocytes in the hemolymph. However, the extraction of hemolymph from larvae is quite difficult, and the collected material is frequently contaminated with other tissues and gastrointestinal fluids, which complicates counting. Therefore, the present work established a high quality and easily reproducible method of extracting hemolymph from honeybee larvae (Apis mellifera), the extraction with ophthalmic scissors. Extraction methods with the following tools also were tested: 30G needle, fine-tipped forceps, hypodermic syringe, and capillaries tubes. The hemolymph was obtained via an incision on the larvae's right side for all methods, except for the extraction with ophthalmic scissors, in which the hemolymph was extracted from the head region. To assess the purity of the collected material, turbidity analyses of the samples using a turbidimeter were proposed, tested, and evaluated. The results showed that the use of ophthalmic scissors provided the clearest samples and was free from contamination. A reference range between 22,432.35 and 24,504.87 NTU (nephelometric turbidity units) was established, in which the collected samples may be considered of high quality and free from contamination.